Screened of long non-coding RNA related to wool development and fineness in Gansu alpine fine-wool sheep - Zhaohua He; Fangfang Zhao; Hongxian Sun; Jiang Hu; Jiqing Wang; Xiu Liu; Mingna Li; Zhiyun Hao; Zhidong Zhao; Bingang Shi; Feiyan Liu; Shaobin Li (BMC Genomics)
Abstract Wool growth and fineness regulation is influenced by some factors such as genetics and environment. At the same time, lncRNA participates in numerous biological processes in animal production. In this research, we conducted a thorough analysis and characterization of the microstructure of wool, along with long non-coding RNAs (lncRNAs), their target genes, associated pathways, and Gene Ontology terms pertinent to the wool fineness development. The investigation utilized scanning electron microscopy and transcriptomic technology, focusing on two distinct types in Gansu alpine fine-wool sheep: coarse type (group C, MFD = 22.26 ± 0.69 μm, n = 6) and fine type (group F, MFD = 16.91 ± 0.29 μm, n = 6), which exhibit differing wool fiber diameters. The results showed that fine type wool fiber scales were more regularly distributed in rings with large scale spacing and smooth edges, while coarse type wool fiber scales were more irregularly arranged in tiles with relatively rougher edges, and the density of wool scales was greater than that of fine type wool. Furthermore, a comprehensive analysis revealed 164 differentially expressed lncRNAs along with 146 potential target genes linked to these lncRNAs in the skin tissues from groups C and F. Utilizing functional enrichment analysis on the target genes, we successfully identified a number of target genes might be associated with the improvement of wool fineness, such as FOXN1, LIPK, LOC101116068, LOC101106296, KRTAP5.4, KRT71, KRT82, DNASE1L2, which are related to hair follicle development, histidine metabolism, epidermal cell differentiation, oxidative phosphorylation and hair cycle process. Additionally, the interoperability network involving lncRNAs-mRNAs indicated lncRNAs (MSTRG.17445.2, XR_006060725.1, MSTRG.871.1, MSTRG.10907.4) might play a significant role in the wool growth development and fineness improvement process. In conclusion, the research enlarges the current lncRNAs database, providing a new insight for the investigation of wool fineness development in fine-wool sheep.